Effectiveness of Static and Dynamic Weight Shift Balance Strategies to Improve Balance Performance in patients With Stroke- - Sania Maqbool, Hafiz Muhammad Uzair Asghar, Amna Zia, Mamoona Anwar, Qurratulain Mushtaq, Madiha Asghar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To enhance the balance in post stroke patients by the implementation of static and dynamic weight shift balance strategies. Methods: Data from 32 patients who complete selection criteria were included to this study. Study design was Randomized controlled trial (RCT). Written informed consent were taken from every individual participating in this study before performing any physical examination. Patients were allocated into two equal groups. On 1st day balance was assessed by Brunel Balance Assessment (BBA), re-accessed by the end of 3rd week and at 6th week. There were two groups, one is Experimental (Group A) receiving static and dynamic weight shift balance training strategies along with conventional physiotherapy treatment while control group (Group B) receiving only conventional rehabilitation program. Results: The results of the BBA (Brunel Balance Assessment) scale showed statistically significant variations in the pre-post analysis for the experimental group with the p-value less than 0.05. By comparing the BBA scale score of group A and B has shown that there was significant difference between post treatment scores, post treatment mean BBA score was 7.000±1.4142 in group A while 3.6250±1.85742 in group B, with the value of p 0.00, showing that group A is better in improving balance of stroke patients. Conclusion: Implementation of static and dynamic balance strategies has a significant effect on improvement of balance in the patients suffering from stroke.